UJI KINERJA ALAT PENGERING BIJI KAKAO (Theobroma cacao L.) TIPE BAK DI PT. PP. LONDON SUMATRA INDONESIA Tbk. PUNGKOL ESTATE - Dandi Firmansyah A. Karim; Ir. Daniel P. M. Ludong, MSc; Lady C. Ch. E. Lengkey (COCOS, 2022)
ABSTRACT The purpose of this research was 1) To assess the performance of cocoa dryers in PT. Pp. London Sumatra Indonesia Tbk. 2) Calculate the efficiency of drying tool during drying process using body type dryer. The materials used are cocoa beans amounting to 1000 kg and gamal wood as a heat source of 249.02 kg. The results showed that the temperature resulting from this dryer is in the temperature range of 62.59Â°C -68.6Â°C where the moisture content of cocoa beans produced after the drying process in this tool is 7.85 % and the drying rate is 2.94 %/h, within 12 hours of drying and the efficiency of the drying tool is 19.68%. Keyword: Tool performance test; Body type dryer; Cocoa bean drying; Drying efficiency.